Music-Based Procedural Content Generation for Games - Nuno Filipe Bernardino Oliveira (2015)
The generation of content procedurally is still something that is emerging in the academic studies, and it is understood as the creation of content automatically, through algorithmic means. There are many reasons to develop this technic, but, mainly, it is used to decrease the memory used for this matter, as this algorithms can continuosly create great amount of content, using lesser space in disk. This procedure is already used in games to create different levels, maps, missions or, less common, to change the game engine or the NPCs (Non-Player Character) behaviour.Even though most games already use music, it is mostly used as a way of supporting the game and create all the needed environment to enhance the user experience. Games that use music as an input source to create playable content are still rare and, commonly, they have their content generated before and in a static way. Naturally, new games are becoming popular in this process by using the chosen songs to generate different content automatically.The goal of this disseration is to develop a game, in a complete procedural way, through music segments, so it would be possible to distinguish significantly different levels, as well as being able to create an opinion about the usage of music as a procedural content generation. This game will be consisted in different stealth missions where the player has to cross the entire level using the available resources in order to not being seen/caught by the enemies. So, the game will receive a music or a segment of it as an input and through a unique analysys it will collect some important features that will allow each segment to be different. After this process, each level will be generated following these features, allowing it to create diversity in each mission, mainly to change the way the game is meant to be played.